Detection of the Yersinia enterocolitica Bacteria Targeting the myfA and ystA Genes in Contaminated Vegetable Samples using Real-Time PCR to Develop Rapid Detection of Food Poisoning Bacteria - Nurjayadi, Muktiningsih; Anggraeni, Rosita GIo; Putri, Gladys Indira; Declan, Jefferson Lynford; Juliansyah, Dandy Akbar; Fahriza, Tiara; Putri, Adinda Myra Amalia; Berkahingrum, Ayu; Rahmawati, Atikah Nur; Kartika, Irma Ratna; Kurniadewi, Fera; Sukmawati, Dalia; Rahayu, Sri; Saamia, Vira; Wiranatha, I Made; Abomoelak, Bassam; El-Enshasy, Hesham Ali (HAYATI Journal of Biosciences, 2025)
Yersinia enterocolitica is a pathogenic bacterium with the ability to survive and multiply in food in a low-temperature environment that can cause death in humans. In previous studies, the optimum annealing temperature of ymoA, ystA, and ail gene primers with amplicons of 185 bp, 123 bp, and 192 bp, respectively, was successfully found. This study aims to develop a pathogenic bacteria detection kit with confirmation, sensitivity, and specificity of myfA and ystA primers in detecting Yersinia enterocolitica bacteria quickly and accurately using the real-time Polymerase Chain Reaction method. The results showed that myfA and ystA primers have optimum annealing temperatures at 60°C with amplicon lengths of 181 bp and 123 bp, respectively. Primer myfA was able to amplify the target with real-time PCR at Ct 12.07±1 and Tm 81±1°C, while the ystA primer at Ct 12.38±1 and Tm 83±1°C. myfA and ystA primers were also able to distinguish target and non-target bacteria based on Ct or Tm. The designed primers successfully detected Yersinia enterocolitica bacteria with the smallest concentration of 0.000439 ng/µL equivalent to 7.024 × 102 CFU. The detection limit obtained is smaller than the contamination threshold set by the Food and Drug Administration (BPOM). Primer myfA and ystA Yersinia enterocolitica also successfully detected the target bacteria in cabbage and lettuce samples artificially. Based on these results, myfA and ystA primers successfully detected Yersinia enterocolitica in vegetable samples using real-time PCR quickly, sensitively, specifically, and accurately.